Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1063/5.0004584
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the ion drag force on dust in magnetized plasmas

Abstract: Modelling the transport of 'dust' particles in a magnetically confined plasma device is an area of active research, and requires a detailed understanding of the forces experienced by dust immersed in a plasma. One of the most significant of these is the 'ion drag force'. Dust transport codes employ a model of this force that was not specifically designed for fusion plasmas, and so does not consider the relevance of strong magnetic fields. However, it is shown here that the effect of magnetic fields on the ion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…From recent simulations and accompanying calculations it is found that the gyro motion of magnetized ions results in a reduced momentum transfer from the ions to the dust. Hence, the ion drag force becomes more and more suppressed by the actions of a magnetic field (James and Coppins 2020). However, this effect seems to become important only when the ion gyro radius is of the order of the particle radius (for a 10 micron dust particle this requires a magnetic field of about 10 T).…”
Section: Forcesmentioning
confidence: 99%
“…From recent simulations and accompanying calculations it is found that the gyro motion of magnetized ions results in a reduced momentum transfer from the ions to the dust. Hence, the ion drag force becomes more and more suppressed by the actions of a magnetic field (James and Coppins 2020). However, this effect seems to become important only when the ion gyro radius is of the order of the particle radius (for a 10 micron dust particle this requires a magnetic field of about 10 T).…”
Section: Forcesmentioning
confidence: 99%
“…In Ref. [36], numerical simulations of ion drag force on a dust grain in magnetized plasma are performed. The authors find that magnetization reduces the drag force, but it remains substantially unvaried for a d /ρ L < 0.1.…”
Section: Scaling Of Turbulent Spreadingmentioning
confidence: 99%